2018
DOI: 10.3390/app8020195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrates on the Dynamic Properties of Inkjet-Printed Ag Thin Films

Abstract: Abstract:The dynamic properties of inkjet-printed Ag thin films on flexible substrates were measured using flexural wave propagation. The Ag nanoparticle suspension was inkjet-printed on polyimide (PI), silicon wafer, and glass. The effects of flexible substrates on the dynamic properties of the films were investigated. Beam-shaped Ag-printed substrates were fabricated by pico-second laser pulse cutting. The wave approach was presented to analyze the vibrations of the thin film on the substrates. The Young's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In the investigation of droplet spreading characteristics, Cui Xinyu observed that the roughness of the substrate predominantly influences the retraction degree and spreading speed of liquid droplets after spreading [ 38 ]. While measuring the dynamic characteristics of inkjet-printed Ag thin films on flexible substrates, Kim D et al discovered that the substrate influences the thickness and surface roughness of Ag films during the sintering process [ 39 ]. Iftimi L. D et al observed that when printing pharmaceuticals, using edible solid foam as a substrate led to improved printing results [ 40 ].…”
Section: Factors Affecting the Quality Of Inkjet Printingmentioning
confidence: 99%
“…In the investigation of droplet spreading characteristics, Cui Xinyu observed that the roughness of the substrate predominantly influences the retraction degree and spreading speed of liquid droplets after spreading [ 38 ]. While measuring the dynamic characteristics of inkjet-printed Ag thin films on flexible substrates, Kim D et al discovered that the substrate influences the thickness and surface roughness of Ag films during the sintering process [ 39 ]. Iftimi L. D et al observed that when printing pharmaceuticals, using edible solid foam as a substrate led to improved printing results [ 40 ].…”
Section: Factors Affecting the Quality Of Inkjet Printingmentioning
confidence: 99%
“…They also found the interlacing overprinting procedure is more advantageous to fabricate thick and narrow nanosilver lines on a hydrophobic substrate. Kim et al conducted measurement of the dynamic properties of inkjet-printed Ag thin films on various substrates such as polyimide, silicon wafer and glass using flexural wave propagation [2]. They fabricated beam-shaped Ag-printed substrates using pico-second laser cutting and measured Young's modulus and loss factor of the Ag thin films using laser Doppler vibrometer without any damage to the thin films.…”
Section: Printed Electronicsmentioning
confidence: 99%